Increased intraoperative epidural pressure in lumbar spinal stenosis patients with a positive nerve root sedimentation sign - Barz, T.; Melloh, Markus; Staub, L.; Lord, S.; Lange, J.; Merk, H. (Springer Verlag, 2014)
Purpose: The sedimentation sign (SedSign) has been shown to discriminate well between selected patients with and without lumbar spinal stenosis (LSS). The purpose of this study was to compare the pressure values associated with LSS versus non-LSS and discuss whether a positive SedSign may be related to increased epidural pressure at the level of the stenosis. Methods: We measured the intraoperative epidural pressure in five patients without LSS and a negative SedSign, and in five patients with LSS and a positive SedSign using a Codman™ catheter in prone position under radioscopy. Results: Patients with a negative SedSign had a median epidural pressure of 9 mmHg independent of the measurement location. Breath and pulse-synchronous waves accounted for 1-3 mmHg. In patients with monosegmental LSS and a positive SedSign, the epidural pressure above and below the stenosis was similar (median 8-9 mmHg). At the level of the stenosis the median epidural pressure was 22 mmHg. A breath and pulse-synchronous wave was present cranial to the stenosis, but absent below. These findings were independent of the cross-sectional area of the spinal canal at the level of the stenosis. Conclusions: Patients with LSS have an increased epidural pressure at the level of the stenosis and altered pressure wave characteristics below. We argue that the absence of sedimentation of lumbar nerve roots to the dorsal part of the dural sac in supine position may be due to tethering of affected nerve roots at the level of the stenosis. © 2013 Springer-Verlag.